#TITLE_ALTERNATIVE# - KARTIKA AVIANTTY (NIM : 10213093), GIFFANI
The common problems of delivering radiation dose in radiotherapy are usually caused by radiation effects that could damage the healthy tissue. Besides of designing a better irradiation technique for radiotherapy, some sensitizer materials have been used to enhance the efficacy of radiotherapy. Nanoparticles of heavy atoms are known as good materials for targeting tumor cell surface, thus have been proved as a proper sensitizer for radiotherapy use. Gold nanoparticles have been investigated as a type of nanoparticle that could enhance radiation dose since it has a high X-ray attenuation coefficient and biocompability. In this study, the effects of gold nanoparticle on the tumor dose enhancement in water phantom were analyzed. A cubic water phantom with dimensions of 20 × 20 × 20 cm3 was simulated and a tumor with 1 × 1 × 1 cm3 dimension was located in 2 cm depth from the surface of water phantom and gold nanoparticles were added into the tumor volume. The tumor was irradiated by 6 and 18 MV photon beams. In this study, tumor and gold nanoparticles were modeled as a homogenous mixture. The results show that gold nanoparticles could enhance the tumor dose in radiation therapy with the enhancements up to 1,061. One of several factors which affect the dose enhancement is gold nanoparticles concentration. If the concentration were enhanced 2,571 times, we obtained tumor dose enhancement of 0,502% – 2,710%. Moreover, higher dose enhancement was also obtained for higher gold nanoparticles concentration because of the higher tumor density resulted higher attenuation and lower penetration of the photon beam. Thus, higher energy could be deposited in the tumor area.